Tivozanib Monotherapy in the Frontline Setting for Patients with Metastatic Renal Cell Carcinoma and Favorable Prognosis - Frazer, Ricky; Arranz, José Ángel; Estévez, Sergio Vázquez; Parikh, Omi; Krabbe, Laura Maria; Vasudev, Naveen S.; Doehn, Christian; Marschner, Norbert; Waddell, Tom; Ince, Will; Goebell, Peter (Current Oncology Reports, 2024)
Purpose of Review: In this review, we discuss which patients with metastatic clear cell renal cell carcinoma (mRCC) may be most suitable for frontline tyrosine kinase inhibitor (TKI) monotherapy, a treatment option supported by emerging long-term efficacy data including overall survival and quality of life. We specifically focus on tivozanib, a potent and selective inhibitor of vascular endothelial growth factor receptor, which has comparable efficacy to other single-agent TKIs in frontline treatment for mRCC while exhibiting fewer off-target side effects. Recent Findings: Combination therapy with TKIs and checkpoint inhibitors (CPIs) and CPI/CPI combination therapies, as well as TKI monotherapy are recommended frontline treatment options for mRCC. Treatment decisions are complex and based on several factors, including the patient’s International Metastatic RCC Database Consortium risk status, age, comorbidities, and personal preferences related to response, tolerability, and quality of life. TKIs not only serve as backbone of most combination therapies for mRCC, but also remain a viable monotherapy option in the first-line setting for patients in favorable risk groups and those with contraindications to CPI combination therapies. Summary: Given that overall survival benefits have not yet been confirmed for CPI-containing combination regimens in favorable risk patients, we argue that frontline single-agent TKI treatment remains a standard of care option for these patients. This is supported by treatment guidelines, even in the era of TKI/CPI combination therapies.
CRIS-Team Scopus Importer:2024-11-29
Keywords: Checkpoint inhibitors; Favorable risk; First-line treatment; Metastatic renal cell carcinoma; Tivozanib; Tyrosine kinase inhibitors